Optimization of the adsorption of lead (II) by hydroxyapatite using a factorial design: Density functional theory and molecular dynamics - El Hammari, L.; Hamed, R.; Azzaoui, K.; Jodeh, S.; Latifi, S.; Saoiabi, S.; Boukra, O.; Krime, A.; Boukra, A.; Saoiabi, A.; Hammouti, B.; Khan, M. M.; et al. (Frontiers in Environmental Science, 2023)
Hydroxyapatite (HAp) synthesized through a wet chemical procedure was used to adsorb lead (II) from an aqueous solution. HAp was characterized using Fourier transform infrared, X-ray diffraction, Brunauer–Emmett–Teller analysis, and scanning electron microscopy. The removal of Pb+2 was investigated using the factorial design approach to investigate the efficiency of different Pb+2 concentrations, adsorption contact time, and HAp mass. The greatest Pb+2 removal (98.94%) was obtained at a starting concentration of 50 mg/L, a contact period of 15 min, and a pH of 8. At 323 K, the isothermal adoption module was fitted to the Langmuir isotherms with a regression coefficient (R2) of 0.96. The thermodynamic calculations revealed that the adsorption process was exothermic, spontaneous, and predominantly dominated by chemisorption. Furthermore, the maximum adsorption capacity (Qmax) at equilibrium was 90.18 mg/g, and the adsorption kinetics was specified by a pseudo-second-order kinetic model. Density functional theory and theoretical studies showed that the results of the experiment were correlated by the observation of a much higher negative Eads value for the lead ion adsorbate molecules as they attached to the surface of the adsorbent.